Pediatric Pyoderma Gangrenosum with Splenic and Pulmonary Involvement. Issue 4 (29th April 2013) - Allen, Caroline P.; Hull, Jeremy; Wilkison, Nick; Burge, Susan M.
Abstract An 8‐year‐old boy presented with ulcers on the lip and limbs, scattered pustules, fever, and general malaise. Further investigation revealed splenic and pulmonary lesions. A diagnosis of pyoderma gangrenosum with splenic and pulmonary involvement was made. The authors have not found a previous report of pediatric pyoderma with splenic involvement in the literature.